Producers versus Profiteers:: The Politics of Class in Newfoundland during the First World War - O'Brien, Mike (Acadiensis, 2011)
Abstract During the First World War a widespread public impression that merchants were taking advantage of the conflict to extract excessive profits became a major issue in Newfoundland politics, and a cause of widespread public discontent. The Fishermen’s Protective Union and other labour organizations were able to use the profiteering issue as a catalyst for political mobilization, and by 1917 had succeeded in forcing the state to take a greater role in regulating the economy. While their gains turned out to be short-lived, the episode marked a significant moment in the history of collective action by Newfoundland’s labouring classes.